ANALISIS JALUR KRITIS MENGGUNAKAN METODE CPM (CRITICAL PATH METHOD) UNTUK OPTIMASI WAKTU PENYELESAIAN PEMBANGUNAN GEDUNG BHAYANGKARI POLRES LAMONGAN - Setiawan, Agus; Putra, Dani Pranata; Irawati, Iin; Saputra, Nor Dede Dwi Aditya; Ramadhan, Zhafif Fawwazsatya; Afifah, Risdiana Cholifatul (Universitas PGRI Semarang, 2026)
The construction of the Bhayangkari Police Headquarters in Lamongan is a large-scale project requiring efficient time management. This study aims to analyze the application of the Critical Path Method (CPM) to optimize project completion time. By applying the CPM method, the critical path is identified, which allows for prioritizing activities that significantly affect the overall project duration. The results of this study show that the project, initially planned to be completed in 150 calendar days, can be completed in 122 calendar days. The identification of the critical path reveals 31 activities that directly impact the project's overall duration. This research provides insights into time management in construction projects and recommends optimizing scheduling and resource allocation to ensure timely project completion.